2013
DOI: 10.1021/la3050016
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Composite Materials from Cellulose, Chitosan, and Cyclodextrin: Facile Preparation and Their Selective Inclusion Complex Formation with Endocrine Disruptors

Abstract: We have successfully developed a simple and one step method to prepare high performance supramolecular polysaccharide composites from cellulose (CEL), chitosan (CS) and (2,3,6-tri-O-acetyl)-α-, β- and γ-cyclodextrin (α-, β- and γ-TCD). In this method, [BMIm+Cl−], an ionic liquid (IL), was used as a solvent to dissolve and prepare the composites. Since majority (>88%) of the IL used was recovered for reuse, the method is recyclable. XRD, FT-IR, NIR and SEM were used to monitor the dissolution process and to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…For reference, the spectrum of CEL powder was also taken (orange curve). It exhibits several distinct different bands at around 1350cm −1 , 1147 cm −1 and 800 cm −1 which can be tentatively, assigned to the O-H bending vibration, the C-O stretching (of the C-OH group) and the C-H stretching, respectively (Duri & Tran, 2013; Harkins et al, 2014; Mututuvari & Tran, 2014; Tran et al, 2013a; Tran et al, 2013b). …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…For reference, the spectrum of CEL powder was also taken (orange curve). It exhibits several distinct different bands at around 1350cm −1 , 1147 cm −1 and 800 cm −1 which can be tentatively, assigned to the O-H bending vibration, the C-O stretching (of the C-OH group) and the C-H stretching, respectively (Duri & Tran, 2013; Harkins et al, 2014; Mututuvari & Tran, 2014; Tran et al, 2013a; Tran et al, 2013b). …”
Section: Resultsmentioning
confidence: 96%
“…Raw sheep wool (untreated), obtained from a local farm, was cleaned by Soxhlet extraction with a 1:1 acetone/ethanol mixture for 48 hrs. [BMIm + Cl − ] was prepared from freshly distilled 1-methylimidazole and n- chlorobutane (both from Alfa Aesar, Ward Hill, MA) using method previously reported ( Duri & Tran, 2013; Haverhals et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the peak derived from the -OH group around 4800 cm −1 of MT and the -OH group around 4900 cm −1 of α CD was broadened (Figure 5(d)). A broadened or shifted peak in the NIR measurement indicated that there were intermolecular interactions between the drug and functional group [17]. This suggested that there were intermolecular interactions between the -CH 2 group and -OH group of MT and the -OH group of α CD in FD (MT/ α CD).…”
Section: Resultsmentioning
confidence: 99%
“…2325 The [CEL+CS] composite obtained was found to be not only biodegradable and biocompatible but also retain unique properties of its component, namely superior mechanical strength (from CEL) and excellent antibacterial and adsorption capability for pollutants and toxins (from CS). 2325 …”
Section: Introductionmentioning
confidence: 99%